THE ANALYSIS OF TOTAL LABOR INFLUENCE AND PERCAPITA INCOME TO THE ECONOMIC GROWTH IN PASAMAN - Yeni, Guspa - (Pendidikan Ekonomi, 2014)
This research aims to analyze: 1) The influence of total labor to economic growth, 2) The influence ofcapital income to the economic growth, 3) The influence of total labor and percapita income simultaneously oneconomic growth in Pasaman. The research is an associative descriptive study. Data used in this research issecondary data, with the type of time series data. The results show: first, the number of workers is significantlyinfluenced on economic growth, which is indicated by the coefficient value of -0.450. This coefficient value issignificant because tcount -4.389 < ttable of 1.745 with significant value of 0.001 < Î± = 0.05, means that Ha isaccepted and H0 is rejected. It means that if the number of workers rose one per cent, the economy expanded at-0.450 units. Second, per capita income have a significant influence on economic growth, which is indicated bythe coefficient value of 0.324. This coefficient value is significant because tcount 6.992 > ttable 1.745 andsignificant value of 0.000 < Î± = 0.05 means that Ha is accepted and H0 is rejected. It means that if the per capitaincome rose one percent, then economic growth will increase by 0, 324 units. Third, Management of TotalLabor and income per capita significantly influence on economic growth, which is indicated by a value of170.141 F count > F table 3.63 and significant value 0.000 < Î± = 0.05, then H0 is rejected and Ha is accepted. Itmeans the number of labour and Per Capita Income, affecting the economic growth of 96% and the rest isexplained by other variables.